ALTERNATIVES OF AN EFFLUENT FROM AN BLECHEAD PULP AND TREATMENTS PAPER INDUSTRY - Flores, Dorotéia Maria Martins (1998)
This paper tried to evaluate the efficiency of the flakelet treatment with aluminum sulphate or ferric chloride for the neutralized brute effluent of a pulp and paper industry. The effluent filtration,  removing fibers, fines macromolecules and natural flakes, permited expressive reductions of the apparent color, real color and COD of the same. While the aluminum sulphate showed excellent results, the ferric chloride didn’t have good performance. It should optimize the concentrations the stirring forms and the flakes decantation. To the samples tested in the first sequence of tests, concentrations around 2,500 ppm of aluminum sulphate (with 14 water molecules of hydration) they showed  excelent results to the reduction of the apparent and real color, COD and clorides. As it was foreseen, in the second sequence of tests, the concentrations of [Al2(SO4)3 . 14 H2O] decresead to all the physicochemical index testad. The best concentration to pH, apparent color and real color was of 1,000 ppm filtrated, while the chorides  it was 2000 ppm  not filtrated, with one minute [1] in high-speed and fifteen [15] minutes in low speed, stirring  time except the real color that was ten [10] minutes in low speed. A recommendation, is suggested to evaluate a sequencial phase of filtration after (clarifloculation/decantation). With this, the performance of a physicochemical treatment of the effluents of this type will be efficient, in spite of the cost involved in the acquisition of aluminum sulphate supply.